Women’s early reproductive behaviors and postpartum depression: a two-sample Mendelian randomization study - Zhenyong Gao; Siyu Deng; Hongliang Zhu; Yong Yang; Ping Yang; Jianbin Du (Critical Public Health)
The relationship between early reproductive behaviors and postpartum depression (PPD) is still unclear. In this study, we explored the causality between reproductive traits and PPD using univariable or multivariable Mendelian randomization (MR) analysis. We selected Single Nucleotide Polymorphisms (SNPs) from genome-wide association study (GWAS) studies targeting age at first sexual intercourse (AFS), age at first live birth (AFB), and age at last live birth (ALB), and age at menarche (AAM) as genetic instruments. Based on inverse variance weighted (IVW) method, the univariate MR results showed that AFS (odds ratio (OR)[95% confidence interval (CI)]: 0.325[0.229–0.461], p < 0.001) and AFB (OR[95%CI]: 0.48[0.289–0.797], p = 0.005) were negatively causally associated with PPD, and no genetic causality was found between ALB and AAM and PPD. After applying MVMR adjusting for education and BMI, we found AFS (OR[95%CI]: 0.589[0.365–0.949], p = 0.029) and AFB (OR[95%CI]:0.533[0.374–0.759], p < 0.001) had a negative causal association with PPD. Our results demonstrated that earlier AFS and AFB have a genetic causal association with PPD. This causality highlights the necessity of promoting reproductive health awareness among adolescent females as a potential strategy to mitigate the risk of PPD.